Glucocorticoid treatment and damage in the anti-neutrophil cytoplasm antibody-associated vasculitides: long-term data from the European Vasculitis Study Group trials. - Robson, J; Doll, H; Suppiah, R; Flossmann, O; Harper, L; Höglund, P; Jayne, D; Mahr, A; Westman, K; Luqmani, R (2014)
OBJECTIVE: Granulomatosis with polyangiitis and microscopic polyangiitis are ANCA-associated vasculitides (AAVs). The Vasculitis Damage Index (VDI) quantifies damage. This study aims to determine the factors associated with long-term damage in the AAVs. METHODS: Data from 535 patients from four European Vasculitis Study Group trials were studied. A long-term follow-up (LTFU) questionnaire at 7 years post-diagnosis was completed. The associations between baseline (age, creatinine and BVAS score) and cumulative (number of relapses and duration of glucocorticoid use) factors and damage accrued (total VDI scores and individual treatment-related damage items) during follow-up were explored. Multiple regressions identified independent associations between baseline measures, cumulative factors and VDI scores at LTFU. RESULTS: Two hundred and ninety-six patients had glucocorticoid use and VDI data available at LTFU, with the mean length of glucocorticoid use being 40.4 months (s.d. 16.7). High levels of damage were independently associated with older age at baseline (P = 0.051), lower glomerular filtration rate (P = 0.041), higher BVAS scores (P = 0.046), increased cumulative glucocorticoid use (P = 0.016) and increasing number of relapses. Patients with longer duration of glucocorticoid treatment were more likely to have a total VDI score ≥5 [odds ratio 1.26 per 12 months of glucocorticoid use (95% CI 1.03, 1.53), P = 0.022]. The main limitation is that approximately half of the patients enrolled had no LTFU data available; these patients were older with more severe initial disease. CONCLUSION: Long-term damage in the AAVs may be associated with severity of initial disease, age, number of relapses and duration of glucocorticoid use.